Development and Validation of a 2D Educational Adventure Game on Dental Health Using the GDLC Method - Novandi Hidayat Hidayat; Dimas Fanny Hebrasianto Permadi (Telkom University, 2025)
Currently, dental and oral health problems in Indonesia are still quite high, because according to the 2018 Basic Health Research Results, the largest proportion of dental problems in Indonesia are damaged/cavities/painful teeth. Oral diseases can cause pain, suffering, psychological obstacles, and social deprivation, which are very detrimental to both individuals and citizens, including children. Poor oral conditions, such as many cavities, can disrupt daily activities. The purpose of this research is that games created using the Game Development Lifecycle (GDLC) method can convey information to users, and when played by players, the gameplay stage will be examined using the Blackbox Testing method. The creation of an educational adventure game project plays an important role in increasing insight by utilizing technology to understand the science of dental and oral diseases. The party involved in this research is a dental expert to validate this game according to valid material. With this research, results can be obtained with a validity value on the educational game material and a feasibility value. Later, the percentage value will determine whether this game is good or bad, using the Game Development Lifecycle (GDLC) methodology. Of the two dentists who have validated the material in the Denterra educational game, the average result of expert validation reached 91% valid, meaning the material in this educational game is Very Feasible according to the Achievement Level Conversion Table. The results of Blackbox Testing reached a value of 94% or 237/252, with features that are less agree that the feature is functional for players are the